2006
DOI: 10.1007/s00011-005-0010-8
|View full text |Cite
|
Sign up to set email alerts
|

YKL-40, a biomarker of inflammation, is elevated in patients with type 2 diabetes and is related to insulin resistance

Abstract: Objective and design. YKL-40 participates in infl ammatory states and vascular processes, which implies that comparison can be made with other infl ammatory markers associated with insulin resistance and type 2 diabetes (T2D). In the present study levels of plasma YKL-40 and serum hsCRP were evaluated in patients with T2D. Materials and methods. Patients with T2D and age-matched healthy controls participated in the study. Insulin resistance was estimated using HOMA-IR model. Biochemical parameters were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
127
6
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(151 citation statements)
references
References 68 publications
15
127
6
3
Order By: Relevance
“…YKL-40 protein also accumulates in serum from patients with other diseases such as rheumatoid arthritis 34 or type 2 diabetes. 35 Determining levels of CHI3L1 mRNA from cancer tissue together with its concentration in serum might enhance sensitivity of this promising biomarker. PI3, the gene encoding for elafin, a whey-acidic-protein (WAP) motif protein, is induced >12-fold in VEGF siRNA tumors.…”
Section: Discussionmentioning
confidence: 99%
“…YKL-40 protein also accumulates in serum from patients with other diseases such as rheumatoid arthritis 34 or type 2 diabetes. 35 Determining levels of CHI3L1 mRNA from cancer tissue together with its concentration in serum might enhance sensitivity of this promising biomarker. PI3, the gene encoding for elafin, a whey-acidic-protein (WAP) motif protein, is induced >12-fold in VEGF siRNA tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of evidence indicates that YKL-40 participates in processes during the early stages of atherosclerosis, and it seems to be of pathogenic importance in the low-grade inflammation that precedes the development of cardiovascular disease (11)(12)(13)(14). We have previously found significantly elevated levels of YKL-40 in patients with type 2 diabetes and an independent positive correlation with insulin resistance and parameters of the lipid profile (15,16).…”
Section: Diabetes Care 32:323-328 2009mentioning
confidence: 95%
“…However, previous studies either have not shown or have shown only a weak correlation between YKL-40 and hsCRP (r ϭ 0.17, NS, and r ϭ 0.22, P Ͻ 0.0001, respectively) (15,16), and hsCRP levels have not previously been found to influence the predictive value of YKL-40 in terms of overall or cardiovascular mortality (16). Therefore, we would not expect different outcomes if we included hsCRP in the analyses.…”
Section: -Median Levels (Interquartile Range) Of Ykl-40 In the Three mentioning
confidence: 97%
See 1 more Smart Citation
“…Thus our results do not provide a rationale for prevention studies using IL-1β antibodies [5] in humans with type 2 diabetes mellitus. On the other hand, type 2 diabetes mellitus is a heterogeneous disease and it cannot be ruled out that an inflammatory background represents a component of the disease process in some patients [27,28].…”
Section: Discussionmentioning
confidence: 99%